Detection of Viable and Total Bacterial Community in the Pit Mud of Chinese Strong-Flavor Liquor Using Propidium Monoazide Combined With Quantitative PCR and 16S rRNA Gene Sequencing - Tan, Guangxun; Zhou, Rui; Zhang, Wenqian; Hu, Yuanliang; Ruan, Zhiyong; Li, Jing; Zhang, Changyi; Shen, Dengjin; Peng, Nan; Liang, Yunxiang; Zhao, Shumiao (Frontiers in Microbiology, 2020)
Microbiota in the pit mud (PM) plays crucial role in the production of Chinese strong-flavor liquor (CSFL), the most popular distilled liquor in China. However, previous studies used total microbe, instead of viable ones, for the characterization of microbial community in this environment. In this study, we used propidium monoazide (PMA) combined with qPCR and 16S rRNA gene sequencing to verify the effect of non-viable bacteria on the characterization of PM bacteria. After PMA concentration optimization, 50 μM PMA was chosen to pretreat 5-year and 20-year PMs. The qPCR results showed that there were 50.78% and 71.84% of non-viable bacteria in the 5-year PM and 20-year PM, respectively. Both copy numbers of total bacteria and viable bacteria were significantly higher in 20-year PM than those in 5-year PM. Nevertheless, in terms of bacterial diversity and composition analyses at OTU level, phyla, classes, and genera levels, 16S rRNA gene sequencing results displayed no significant differences between total bacteria and viable bacteria in both PM types. In conclusion, it is necessary for non-viable bacteria to be considered in determining absolute biomass of bacteria in PM, but not necessary in the analysis of diversity and composition of PM bacteria. To the best of our knowledge, our study is the preliminary attempt to analyze viable bacteria in the PM of CSFL, and provides useful information on how to accurately characterize microbial community in PM environment.